2002
DOI: 10.1200/jco.2002.12.112
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Plus Carboplatin Versus Gemcitabine Plus Paclitaxel in Advanced Non–Small-Cell Lung Cancer: A Phase III Randomized Trial

Abstract: The PG combination is as equally active and well tolerated as the PC combination in patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
115
1
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(128 citation statements)
references
References 29 publications
9
115
1
3
Order By: Relevance
“…Standard premedication with dexamethasone at a dose of 20 mg given orally 12 and 6 h prior to paclitaxel infusion has been shown to prevent HSR in most cases (Weiss et al, 1990;Rowinsky and Donehower, 1995;Kintzel, 2001). Despite this premedication schedule, grade 3/4 HSR still occur in 1 -2% of patients (Kosmidis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Standard premedication with dexamethasone at a dose of 20 mg given orally 12 and 6 h prior to paclitaxel infusion has been shown to prevent HSR in most cases (Weiss et al, 1990;Rowinsky and Donehower, 1995;Kintzel, 2001). Despite this premedication schedule, grade 3/4 HSR still occur in 1 -2% of patients (Kosmidis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of males varied within the range of 51%-93%. Most patients had stage IIIB or IV NSCLC; inoperable stage IIIA disease was also admitted in three studies [35,45,62], whereas stage IIIB disease was excluded in one trial [47].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…discontinued treatment early because of voluntary withdrawal or drug toxicity [32,35]. Finally, two studies published in abstract form excluded patients for whom data were not available and/or with insufficient follow-up [37,54].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Moreover, the toxicity profile of cisplatin can influence the patients' quality of life. Several randomised phase III studies have demonstrated that nonplatinum-containing regimens have substantial efficacy against advanced/metastatic NSCLC with a more favourable toxicity profile than the corresponding cisplatin-based regimens (Douillard et al, 2001;Georgoulias et al, 2001Georgoulias et al, , 2005Kosmidis et al, 2002).…”
mentioning
confidence: 99%